Applications of ring closing metathesis. Total synthesis of (±)-pseudotabersonine. Issue 39 (30th September 2015) - Cheng, Bo; Sunderhaus, James D.; Martin, Stephen F.
Abstract: A novel approach to the Aspidosperma family of alkaloids was developed and applied to a concise total synthesis of (±)-pseudotabersonine that was accomplished in 11 steps. Key transformations include a stepwise variant of a Mannich-like multicomponent assembly process, a double ring-closing metathesis sequence, and a one-pot deprotection/cyclization reaction. Graphical abstract: